The Analysis of Teaching and Learning Reading Through Think-Aloud Method - Satria Adi Pradana (IAIN Syekh Nurjati Cirebon, 2017)
Abstract: Reading is needed by people around the world. The objectives of this research were to know process teaching and learning reading of using think-aloud method, to know teacher’s problem in teaching reading of using think-aloud method and to know students’ problem in learning reading of using think-aloud method. Qualitative was used in this research as a research design. Purposive sampling technique was used to determine the sample. The class of VIII K was chosen as a sample which consisted of 37 students. In collecting the data, observation, interview and documentation were used. Three major phases of data analysis were used in this research, they were: data reduction, data display and data conclusion. This research was conducted in two meeting. After analyzing the data, there were three points of the result. First, the teacher did not apply some of steps in observation checklist, but it did not give the big influence in teaching and learning process. Second, the teacher’s problem in teaching reading through think-aloud method were that the teacher had difficulty to handle the students in giving instruction to ask and also the teacher felt difficulty to manage the time in implementing think-aloud method in teaching reading. Third, the problem faced by the students in learning reading through think-aloud method was that the students could not remember information from the text although they were using think-aloud method. Keywords: Think-aloud method, teaching reading, qualitative research.